Reduction of Losses in the Distribution of Dairy Products as Part af Product Management - Lipińska, Milena; Krajewski, Karol (Studia Oeconomica Posnaniensia, 2017)
Managing product distribution processes in the diary chain is an essential area of product management processes, and it involves the possibility of reducing the losses of such products. Thus far, the available literature has been void of information on the relations between these occurrences, which prompted the authors to undertake an analysis of the aforementioned processes as well as to conduct an empirical investigation. The purpose of the investigation was an analysis of the conditions for the distribution of the products and the methods of managing dairy products at a selected distribution centre, using the loss risk analysis and the Ishikawa Diagram, in order to identify the locations and volumes of losses concerning these products. The investigation was conducted at a specialised dairy centre in the vicinity of Siedlce, in 2013 and 2014. Internal documents concerning controlling the conditions for the transport processes were subjected to a detailed analysis. On this basis, an analysis of quality loss risk exposures in the transport and storage of dairy products at the distribution centre were carried out. The losses of dairy products were assessed at the level of 0.64% of the volume of the distributed products. However, the need to reduce losses in the distribution processes of dairy products requires that new product management procedures be developed in order to ensure the quality of these products.